Global transcriptomic changes occur in uterine fluid-derived extracellular vesicles during the endometrial window for embryo implantation. Issue 8 (30th June 2021) - Giacomini, E; Scotti, G M; Vanni, V S; Lazarevic, D; Makieva, S; Privitera, L; Signorelli, S; Cantone, L; Bollati, V; Murdica, V; Tonon, G; Papaleo, E; et al.
Abstract: STUDY QUESTION: Are uterine fluid-derived extracellular vesicles (UF-EVs) a 'liquid biopsy' reservoir of biomarkers for real-time monitoring of endometrial status? SUMMARY ANSWER: The transcriptomic cargo of UF-EVs reflects the RNA profile of the endometrial tissue as well as changes between the non-receptive and the receptive phase, possibly supporting its use for a novel endometrial receptivity test. WHAT IS KNOWN ALREADY: EVs have been previously isolated from uterine fluid, where they likely contribute to the embryo-endometrium crosstalk during implantation. Based on a meta-analysis of studies on endometrial tissue implantation-associated genes and the human exosomes database, 28 of the 57 transcripts considered as receptivity markers refer to proteins present in human exosomes. However, the specific transcriptomic content of receptive phase UF-EVs has yet to be defined. STUDY DESIGN, SIZE, DURATION: Two experimental series were set up. First, we simultaneously sequenced RNA species derived from paired UF-EVs and endometrial tissue samples collected from physiologically cycling women. Second, we analyzed RNA species of UF-EVs collected during the non-receptive (LH + 2) and receptive (LH + 7) phase of proven fertile women and from the receptive (LH + 7) phase of a population of women undergoing ART and transfer of euploid blastocysts. PARTICIPANTS/MATERIALS, SETTING, METHODS: For paired UF—endometrial tissue sampling, endometrial tissue biopsies were obtained with the use of a Pipelle immediately after UF collection performed by lavage of the endometrial cavity. Overall, n = 87 UF samples were collected and fresh-processed for EV isolation and total RNA extraction, while western blotting was used to confirm the expression of EV protein markers of the isolated vesicles. Physical characterization of UF-EVs was performed by Nanoparticle Tracking Analysis. To define the transcriptomic cargo of UF-EV samples, RNA-seq libraries were successfully prepared from n = 83 UF-EVs samples and analyzed by RNA-seq analysis. Differential gene expression (DGE) analysis was used to compare RNA-seq results between different groups of samples. Functional enrichment analysis was performed by gene set enrichment analysis with g:Profiler. Pre-ranked gene set enrichment analysis (GSEA) with WebGestalt was used to compare RNA-seq results with the gene-set evaluated in a commercially available endometrial receptivity array. MAIN RESULTS AND THE ROLE OF CHANCE: A highly significant correlation was found between transcriptional profiles of endometrial biopsies and pairwise UF-EV samples (Pearson's r = 0.70 P < 0.0001; Spearman's ρ = 0.65 P < 0.0001). In UF-EVs from fertile controls, 942 gene transcripts were more abundant and 1305 transcripts less abundant in the LH + 7 receptive versus the LH + 2 non-receptive phase. GSEA performed to evaluate concordance in transcriptional profile between the n = 238 genes included in the commercially available endometrial receptivity array and the LH + 7 versus LH + 2 UF-EV comparison demonstrated an extremely significant and consistent enrichment, with a normalized enrichment score (NES)=9.38 ( P < 0.001) for transcripts up-regulated in LH + 7 in the commercial array and enriched in LH + 7 UF-EVs, and a NES = −5.40 ( P < 0.001) for transcripts down-regulated in LH + 7 in the commercial array and depleted in LH + 7 UF-EVs. When analyzing LH + 7 UF-EVs of patients with successful versus failed implantation after transfer of one euploid blastocyst in the following cycle, we found 97 genes whose transcript levels were increased and 64 genes whose transcript levels were decreased in the group of women who achieved a pregnancy. GSEA performed to evaluate concordance in transcriptional profile between the commercially available endometrial receptivity array genes and the comparison of LH + 7 UF-EVs of women with successful versus failed implantation, demonstrated a significant enrichment with a NES = 2.14 ( P = 0.001) for transcripts up-regulated in the commercial array in the receptive phase and enriched in UF-EVs of women who conceived, and a not significant NES = −1.18 ( P = 0.3) for transcripts down-regulated in the commercial array and depleted in UF-EVs. In terms of physical features, UF-EVs showed a homogeneity among the different groups analyzed except for a slight but significant difference in EV size, being smaller in women with a successful implantation compared to patients who failed to conceive after euploid blastocyst transfer (mean diameter ± SD 205.5± 22.97 nm vs 221.5 ± 20.57 nm, respectively, P = 0.014). LARGE SCALE DATA: Transcriptomic data were deposited in NCBI Gene Expression Omnibus (GEO) and can be retrieved using GEO series accession number: GSE158958. LIMITATIONS, REASONS FOR CAUTION: Separation of RNA species associated with EV membranes might have been incomplete, and membrane-bound RNA species—rather than the internal RNA content of EVs—might have contributed to our RNA-seq results. Also, we cannot definitely distinguish the relative contribution of exosomes, microvesicles and apoptotic bodies to our findings. When considering patients undergoing ART, we did not collect UFs in the same cycle of the euploid embryo transfer but in the one immediately preceding. We considered this approach as the most appropriate in relation to the novel, explorative nature of our study. Based on our results, a validation of UF-EV RNA-seq analyses in the same cycle in which embryo transfer is performed could be hypothesized. WIDER IMPLICATIONS OF THE FINDINGS: On the largest sample size of human EVs ever analyzed with RNA-seq, this study establishes a gene signature to use for less-invasive endometrial receptivity tests. This report is indeed the first to show that the transcriptome of UF-EVs correlates with the endometrial tissue transcriptome, that RNA signatures in UF-EVs change with endometrial status, and that UF-EVs could serve as a reservoir for potential less-invasive collection of receptivity markers. This article thus represents a step forward in the design of less-invasive approaches for real-time monitoring of endometrial status, necessary for advancing the field of reproductive medicine. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by a competitive grant from European Society of Human Reproduction and Embryology (ESHRE Research Grant 2016-1). The authors have no financial or non-financial competing interests to disclose. TRIAL REGISTRATION NUMBER: NA.